1991
DOI: 10.1007/bf02206868
|View full text |Cite
|
Sign up to set email alerts
|

A comparison and evaluation of three commonly used autism scales

Abstract: Reliability and validity of three commonly used autism scales, the Autism Behavior Checklist (Krug, Arick, & Almond, 1980), the Real Life Rating Scale (Freeman, Ritvo, Yokota, & Ritvo, 1986), and the Childhood Autism Rating Scale (Schopler, Reichler, & Renner, 1988), were investigated. Data analyses were based on completed protocols for 24 children or adolescents who met DSM-III-R criteria for pervasive developmental disorders. First, to replicate previous findings, interrater reliability of each of the two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 11 publications
4
47
2
1
Order By: Relevance
“…3,4,[15][16][17][18] The CARS is widely used for screening and diagnostic purposes, but it was not designed to measure behavior change. Although some studies have reported that certain areas may be sensitive to change, 13,15 the subjective nature of the ratings, broadly defined categories, and (perhaps) lack of normative data may reduce the scale's appeal.…”
Section: Objectives Of the Trialmentioning
confidence: 99%
“…3,4,[15][16][17][18] The CARS is widely used for screening and diagnostic purposes, but it was not designed to measure behavior change. Although some studies have reported that certain areas may be sensitive to change, 13,15 the subjective nature of the ratings, broadly defined categories, and (perhaps) lack of normative data may reduce the scale's appeal.…”
Section: Objectives Of the Trialmentioning
confidence: 99%
“…[13][14][16][17][18][19] The results of such studies, however, vary significantly regarding the sample selection criteria and methodology.…”
Section: -21mentioning
confidence: 99%
“…Two studies [13][14][15][16][17][18][19][20][21] correctly classified 100% and 85%, respectively, of the children evaluated. However, such results were not obtained in other studies, [14][15][16][17] in which only 50% of the children were correctly classified. Neither speaking nor nonspeaking autistic children were correctly classified at cutoff point 68.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…Autism Behavior Checklist (ABC) (Attacment 1) developed by Krug et al (8) is one of the scales frequently referred to for scanning and evaluation of education in autism in many countries. There are 57 items defining autistic symptoms in Autism Behavior Checklist.…”
Section: Introductinmentioning
confidence: 99%